Prognostic significance of serial high-sensitivity troponin I measurements following acute cardiac decompensation-correlation with longer-term clinical outcomes and reverse remodelling. (1st April 2017) - Wallenborn, Julia; Marx, Almuth; Störk, Stefan; Güder, Gülmisal; Brenner, Susanne; Ertl, Georg; Angermann, Christiane E.
Abstract: Background: This study investigated the correlation of levels of and changes in serial high-sensitivity cardiac troponin I (hsTnI) with subsequent clinical event rates and changes in cardiac morphology and function in patients hospitalized for acutely decompensated heart failure (ADHF). Methods and results: HsTnI levels were determined in 875 ADHF patients before discharge from hospital (baseline cohort) and clinical outcomes assessed after 180 days. HsTnI was re-measured at 180 days in 456/875 patients (follow-up cohort). Follow-up hsTnI values were grouped according to baseline hsTnI tertiles; echocardiographic changes from 0–180 days and event rates from 180–540 days were assessed in these subgroups. At baseline and 180-day follow-up, hsTnI levels were elevated (> 0.06 ng/mL) in 322/875 (37%) and 68/456 (15%) patients, respectively. At 180 days, 85/875 patients (9.7%) had died (cardiovascular causes: 56/875 [6.4%]). Hazard ratios (HR) and 95% confidence intervals (CI) for all-cause and cardiovascular mortality (per two-fold hsTnI increase) were 1.2 (1.0–1.3; p = 0.004) and 1.2 (1.1–1.4; p = 0.001), respectively. In the follow-up cohort, 35/456 patients (7.7%) died between days 180 and 540 (cardiovascular death: 20/456, 4.4%). HsTnI was a significant predictor of cardiovascular re-hospitalization within 180–540 days (HR 1.2, 95% CI 1.0–1.4; p = 0.028). Patients with hsTnI in the lowest tertile at follow-up had more frequent and more pronounced reverse cardiac remodelling on echocardiography. Conclusions: Elevated baseline hsTnI was common and associated with adverse clinical outcomes. Changes in hsTnI from baseline to 180-day follow-up predicted longer-term risk. Low or decreasing hsTnI was associated with better reverse cardiac remodelling and more favourable long-term outcomes. Clinical Trial Registration URL: http://www.controlled-trials.com . Unique identifier: ISRCTN23325295.